A stable and efficient 3D cobalt-graphene composite catalyst for the hydrolysis of ammonia borane. Issue 19 (20th July 2016) - Li, Mengxiong; Hu, Jiantong; Lu, Hongbin
Abstract : We synthesized a PEI decorated GO 3D composite supported cobalt catalyst that showed high catalytic activity and stability for the hydrolysis of AB. Abstract : Low-cost, stable and highly efficient catalysts are essential for practical energy applications. In this study, branched polyethylenimine (PEI)-decorated graphene oxide (GO) 3D structures were prepared through a hydrothermal reaction. Cobalt (Co) nanoparticles (NPs) were deposited on the PEI-GO 3D structures, forming the desired, low-cost composite catalyst PEI–GO3D /Co. The catalyst shows a quite high catalytic activity for the room temperature hydrolysis of ammonia borane, with a turnover frequency of 18.5 molH2 min −1 molCo −1 and a hydrogen generation rate of 7.68 LH2 min −1 gCo −1 . The activation energy of the catalyst is relatively low (27.41 kJ mol −1 ), along with an ultrahigh cycle stability, that is, ∼83% of the initial catalytic activity was retained after 5 catalytic cycles, superior to the majority of non-noble metal catalysts.